Covalent organic framework supported Pd(II)‐catalyzed conjugate additions of arylboronic acids to α, β‐unsaturated carboxylic acids. (22nd April 2021) - Wen, Min; Lu, Shujuan; Fan, Chaogang; Shen, Kai; Lin, Shaohui; Pan, Qinmin
Abstract : A palladium(II)‐coordinated covalent organic framework (Pd(II)@COF) was mechanochemically synthesized from [2, 2′‐bipyridine]‐5, 5′‐diamine (Bpy) and 1, 3, 5‐triformylphloroglucinol (Tp), which was demonstrated as a catalyst for conjugate addition of arylboronic acids to unreactive α, β‐unsaturated carboxylic acids in aqueous media (water/acetone = 1:1). Modest to good yields were obtained for most substrates, and studies on the catalyst recyclability showed that the heterogeneous catalyst gave >80% yields in the first 4 cycles. This research broadens the application of COFs supported catalysis and gave a new option for Pd(II)‐catalysis. Abstract : Palladium(II)‐coordinated covalent organic framework (Pd(II)@COF) was mechanochemically synthesized from [2, 2′‐bipyridine]‐5, 5′‐diamine (Bpy) and 1, 3, 5‐triformylphloroglucinol (Tp), which was demonstrated as a catalyst for conjugate addition of arylboronic acids to unreactive α, β‐unsaturated carboxylic acids in aqueous media (water/acetone = 1:1). Modest to good yields were obtained for most substrates, and studies on the catalyst recyclability showed that the heterogeneous catalyst gave >80% yields in the first 4 cycles.